O papel da cinematografia estrangeira na intensificação do anticomunismo no Brasil: uma análise das narrativas fílmicas e conflitos políticos durante da guerra fria (1947-1960) - Pavani, Luana Casemiro (2023)
At the end of the 1940s, newspaper reports of stoning and vandalism in Brazilian cinemas became increasingly frequent. Iron Curtain (Dir.: William A. Wellman, 1948) and Traitor (Dir.: Victor Saville, 1949) are just some of the films that caused controversy by making explicit the propagation of US anti-communism in foreign countries, including Brazil. The fear of the expansion of the communist system after the end of the Second World War ensured that intense political manifestations remained in American culture, which in turn used cinema as its main means of spreading ideology. With the help of numerous cultural agreements established between the countries, the export of American feature films "was the result of a certain enthusiasm with the assessment that films were the best way to bring the two countries closer together" (Valim, 2017, p. 267), as well as shaping public opinion and influencing Brazilian socio-politics in a comprehensive way